2020
DOI: 10.1186/s12917-020-02372-w
|View full text |Cite
|
Sign up to set email alerts
|

Association among biofilm formation, virulence gene expression, and antibiotic resistance in Proteus mirabilis isolates from diarrhetic animals in Northeast China

Abstract: Background The aim of this study was to investigate the association among biofilm formation, virulence gene expression, and antibiotic resistance in P. mirabilis isolates collected from diarrhetic animals (n = 176) in northeast China between September 2014 and October 2016. Results Approximately 92.05% of the isolates were biofilm producers, whereas 7.95% of the isolates were non-producers. The prevalence of virulence genes in the biofilm producer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
6
33
3
Order By: Relevance
“…The PCR proved that the recovered P. mirabilis strains are virulent and harbored atp D , ure C , rsb A , and zap A virulence genes with a prevalence of 100%, 100%, 94.3%, and 91.4%, respectively. Our findings are nearly agreed with those reported by Pathirana 30 and Sun 51 . The atp D gene is encoded for ATP synthase β-subunit for the production of ATP from ADP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The PCR proved that the recovered P. mirabilis strains are virulent and harbored atp D , ure C , rsb A , and zap A virulence genes with a prevalence of 100%, 100%, 94.3%, and 91.4%, respectively. Our findings are nearly agreed with those reported by Pathirana 30 and Sun 51 . The atp D gene is encoded for ATP synthase β-subunit for the production of ATP from ADP.…”
Section: Discussionsupporting
confidence: 93%
“…The resistance to polymyxins is common in the mutant P. mirabilis due to the alteration of LPS that is controlled by the expression of the ept C gene and the modification of the L- Ara4N. However, several previous studies reported the sensitivity of some P. mirabilis isolates to polymyxins, especially those of animal origin as reported by Sun 51 . The ept C gene may be present but not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of 66.7% is lower compared to similar findings of Pathirana et al (Pathirana et al, 2018) who isolated Proteus species from humans and pet turtles and reported 91.7% prevalence for ureC genes. Gene expression of ureC genes and other virulent genes in Multidrug resistant P. mirabilis isolated from diarrhetic animals in North East China were was associated to biofilm formation (Sun et al, 2020). The rsbA gene was amplified in both P. mirabilis and P. vulgaris with a 26.7% frequency which is in contrast to the report of Abbas et al (Abbas et al, 2015), who reported that rsbA gene could not be amplified in P. mirabilis and P.…”
Section: Discussionmentioning
confidence: 61%
“…less than 8% of uncomplicated UTIs is caused by Proteus mirabilis, a major pathogen often isolated from patients with complicated UTIs, i.e., those with functional or anatomic abnormalities of or with chronic foreign bodies in the urinary tract (5). As a motile gram-negative bacillus belonging to the family Enterobacteriaceae, P. mirabilis represents an opportunistic pathogen frequently found in intestinal tracts (6). P. mirabilis is considered a major cause of UTIs and the primary infectious factor in patients with indwelling urinary catheters (7).…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharides and hemolysins are also two important virulence factors that allow bacteria to attach to cells and colonize tissues, thus exacerbating pathogenesis. It should be noted, however, that the pathogenicity of this bacterium is not solely due to virulence genes; biofilm formation is also one of the main factors in the pathogenicity of P. mirabilis, which plays an important role in the persistence of infection and the occurrence of inflammatory reactions (6). After bacterial colonization, the catheter may enter the bladder, setting the stage for UTI (8).…”
Section: Introductionmentioning
confidence: 99%